Kebijakan fiskal di indonesia: Dampak dan Tantangan dalam Mewujudkan Pertumbuhan Ekonomi Berkelanjutan - Rihani, Nevira Ayu (Maliki Interdisciplinary Journal, 2025)
Fiscal policy in Indonesia plays a crucial role in achieving sustainable economic growth. This policy includes the regulation of state revenues through taxes and government expenditures for various development programs. In recent years, Indonesia has experienced significant changes in its fiscal policy, particularly in the context of post-COVID-19 economic recovery. This study aims to analyze the impact of fiscal policy on economic growth and the challenges faced in its implementation. The results indicate that expansive fiscal policy, especially in infrastructure spending and social programs, can drive economic growth. However, challenges such as reliance on foreign debt and inefficient budget management remain obstacles. This study recommends the need for more planned and sustainable fiscal policy reforms to ensure inclusive economic growth in Indonesia.